Interactive Effects of Palm Kernel Cake Ratio and Enzyme Supplementation on Broiler Chicken Performance - Baskara, Aji Praba; Siti Zubaidah; Bambang Ariyadi; Chusnul Hanim; Zuprizal (Jurnal Sain Peternakan Indonesia, 2025)
This study investigated the interactive effects of palm kernel cake (PKC) inclusion levels (10 and 20%) and enzyme supplementation (NSPase, protease, and mannanase) on the growth performance and nutrient efficiency of broiler chickens. A total of 720 male broilers were randomly assigned to four dietary treatments and 6 replicates per treatment with each treatment consisting of 30 chickens for 28 days in a completely randomized design. The parameters measured included feed intake, body weight gain, feed conversion ratio (FCR), energy and protein intake, and their respective efficiencies (Protein Efficiency Ratio (PER) and Energy Efficiency Ratio (EER)). Results showed that broilers fed diets with 10% PKC—both with and without enzyme supplementation—achieved significantly better final body weight, average daily gain (ADG), FCR, EER, and PER than those fed 20% PKC (P<0.05). Notably, enzyme supplementation improved nutrient utilization only at the 10% PKC level, while the 20% PKC inclusion led to reduced digestibility and performance, regardless of enzyme use (P<0.05). Feed, energy, and protein intake were not significantly different across treatments, indicating that variations in growth were primarily due to nutrient utilization efficiency (P>0.05). These findings suggest that a 10% PKC inclusion with or without enzymes optimizes broiler performance, while higher PKC levels may negate enzyme benefits due to increased fibre content.